IDENTIFICATION OF ONLINE-BASED MATHEMATICS LEARNING PROCESS REVIEWED FROM JUNIOR HIGH SCHOOL STUDENT LEARNING OUTCOMES - Pandega, Siwi Nur; Isnaeni, Nadia; Yanti, Fitri Dwi; Rizkiani, Rizka; Pramesthi, Dewi; Rahmawati, Fadhilah (Tesseract: International Journal of Geometry and Applied Mathematics, 2024)
This study aims to describe the identification of the mathematics learning process in junior high school students during online learning in terms of learning outcomes.  This study uses a qualitative descriptive approach.  The data analysis technique used a questionnaire with google forms and a comparison of student scores during online learning and before online learning.  The subjects of this study were students of grade 8 SMP Eka Sakti Semarang.  The number of students was 67 people from two different classes.  The results show that online learning is considered to be the solution for teaching and learning activities to continue in the midst of this pandemic.  Based on the results of data analysis, it can be concluded that the online-based mathematics learning process of junior high school students using Google Classroom includes three stages, namely the preliminary stage in the form of learning preparation, the core stage in the form of learning methods, and the evaluation stage in the form of learning outcomes for students.  Student learning outcomes before face-to-face online learning were higher than when learning online using Google Classroom.  The cause of low online learning outcomes is because when online applications are too complex students are unable to learn mathematics optimally, as well as when there is a lot of data that must be conveyed but internet or network access becomes slow, of course this will interfere with student activities.